DIRETRIZES PARA MODELAGEM 3D DIRECIONADA A OTIMIZAÇÃO DO PROCESSO DE QUANTIFICAÇÃO - Giesta, Josyanne P.; Lira, Emilha C. F. da S.; Costa, Thalita G.; Silva, Jessyka A. A. da (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The process of quantification of engineering services are of great relevance for the development of the budget of the work and for the physical-financial schedule, with the definition of the term of execution of the enterprise. However, in spite of all its importance, the quantitative survey is still very individualized, that is, without a standardization of quantification criteria. In this way, it is a job that requires a qualified professional, with experience in constructive techniques and who has an excellent view of projects, this being a time consuming and susceptible to errors and omissions process, besides presenting great difficulty to the conference. Studies have pointed out the possibility of insertion of BIM in this activity, with a perspective of great advantages, due to the ease of extraction of information from 3D models. Nevertheless, more detailed studies that present guidelines that can guide companies and professionals in the quantification process through BIM models are scarce. In this context, the present article proposes to develop, based on bibliographical review and in a case study, a flowchart with guidelines that guide the quantification process via BIM models.